1986
DOI: 10.1252/jcej.19.507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fine Bubbles on Flow Properties in Bubble Column With Suspended Solid Particles

Abstract: Flowproperties in a dissolver for direct coal liquefaction were simulated by using a cold bubble column of 12 cm i.d. To generate small gas bubbles in the column, a surfactant was added to tap water and a gas distributor with fine holes was employed. Whenglass spheres of 44 and 113 /nn dia. were suspended in the presence of the surfactant, the gas holdup was 1.5-4 times that for the tap water system, and the axial dispersion coefficient of liquid showed a minimum at superficial gas velocities of 3-5 cmà"s~*. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 1 publication
0
16
0
Order By: Relevance
“…The difference disappeared with increasing operating pressure. Koide et al ( 1979) and Ueyama et al (1980) Yu and Kim (1988) observed that bubble chord length in the column center was higher than that near the walL…”
Section: Bubble Size and Bu Bble Rising Velocitymentioning
confidence: 99%
See 4 more Smart Citations
“…The difference disappeared with increasing operating pressure. Koide et al ( 1979) and Ueyama et al (1980) Yu and Kim (1988) observed that bubble chord length in the column center was higher than that near the walL…”
Section: Bubble Size and Bu Bble Rising Velocitymentioning
confidence: 99%
“…(Hikita et al, 1980;Miller, 1980;Fan et al, 1985;Reilly et al, 1986;Wachi et al, 1987;Prakash, 1991;Del Pozo, 1992;Gandhi, 1997 (Akita and 'fahida, 1973;Kato et al, 1973;Grover et al. 1986;Hatate et al, 1986;Morooka et al, 1986;Ozturk et al, 1987 2)The design of gas and liquid sparger plays a vital role in limiting the magnitude of the erron. Some gas is capable of flowing into the column after the gas has been hirned off due to higher pressure f o n d inside the distributor before the gas is tumed off.…”
Section: Phase Holdup Measurement Techniquementioning
confidence: 99%
See 3 more Smart Citations